Desarrollo de la investigación celular y molecular del movimiento de ortodoncia presente en la literatura científica; revisión de alcance. (2022)
Introduction: Forces applied during orthodontic treatments produce changes at the cellular and molecular level that have been elucidated through multiple investigations. Objective: To identify the molecular mechanisms reported in the scientific literature, between 2011 and 2021, that occur with the cellular response when there is dental movement and the bone response during the application of forces in orthodontic treatment.